Bladder paraganglioma: a 25-year systematic review unveils the benefits of early diagnosis in reducing surgical complications - Liu, Qingqing; Wang, Tong; Tu, Wenlong; Zhou, Pengfei; Wu, Xionghui; Lv, Huayan (Frontiers in Surgery, 2025)
BackgroundBladder paraganglioma (BPG) is a rare tumor frequently misdiagnosed before surgery. To raise awareness and improve early detection, we systematically reviewed clinical manifestations and treatment approaches reported in BPG case reports over the past 25 years. We aimed to identify factors that could facilitate timely diagnosis and reduce complications from misdiagnosis.Materials and methodsWe searched PubMed for BPG case reports published between January 1, 2000, and December 31, 2024. Two independent reviewers extracted data and performed statistical analyses. Patients were categorized into two groups based on preoperative diagnosis: correctly diagnosed and misdiagnosed.ResultsA total of 199 cases from 184 articles were included, with eighty patients (40.2%) preoperatively diagnosed with BPG and 119 (59.8%) misdiagnosed. Catecholamine-related symptoms were significantly more common in the correctly diagnosed group (60.0% vs. 21.8%, p < 0.001), whereas urinary symptoms were more prevalent in the misdiagnosed group (57.1% vs. 28.7%, p < 0.001). None of the misdiagnosed patients received preoperative α-adrenergic blockade therapy. There were significant differences in surgical approach selection between the two groups: 79.0% of patients in the misdiagnosed group underwent transurethral resection (TUR), while only 14.3% received partial cystectomy; conversely, in the correctly diagnosed group, 77.5% of patients underwent partial cystectomy, and only 15.0% underwent TUR. The correctly diagnosed group had more preoperative preparation (63.7% vs. 0%, p < 0.001), and lower incidences of intraoperative hypertensive crisis (17.5% vs. 40.3%, p < 0.001), discontinued surgeries (0% vs. 26.9%, p < 0.001), residual tumors (2.5% vs. 37.8%, p < 0.001), and reoperations (12.5% vs. 41.2%, p < 0.001). Catecholamine-related symptoms (OR = 3.98, p < 0.001) and hypertension (OR = 2.52, p = 0.015) predicted correct diagnosis while urinary symptoms (OR = 0.44, p = 0.031) were associated with misdiagnosis.ConclusionMore than half of BPG patients lack accurate preoperative diagnoses. Catecholamine-related symptoms were strongly associated with correct diagnosis, while urinary symptoms increased misdiagnosis. Patients with preoperative correct diagnosis more frequently received α-adrenergic blockade and underwent cystectomy rather than transurethral resection, with reduced hypertensive crises, surgery discontinuation, and residual tumors compared with those misdiagnosed. These findings highlight the need for structured catecholamine screening in bladder mass diagnostics and support our diagnostic flowchart to enhance early BPG detection.